Dominican Republic: Agricultural R&D indicators factsheet - Stads, Gert-Jan; de los Santos, Luis (International Food Policy Research Institute, 2022)
The Dominican Republic’s investment in agricultural R&D has been rather stagnant over the past decade (in inflation-adjusted terms). Measured against agricultural GDP, however, there has been a steady drop in investment levels. In 2020, the Dominican Republic spent just 0.18 percent of its agricultural GDP on agricultural R&D, representing among the lowest levels in Latin America and the Caribbean. The Dominican Republic lacks a critical mass of PhD-qualified agricultural researchers. Many scientists with PhD degrees are currently in their sixties and fast approaching the mandatory retirement age. Recruiting and training the next generation of researchers is an urgent priority. However, low public-sector salaries and limited incentives are impeding factors to attracting, motivating, and retaining young talent. Unlike their colleagues at most national agricultural research insti-tutes across Latin America, a high share of IDIAF researchers hold dual appointments as professors or resear-chers at universities or the private sector. This situation discourages universities to create permanent positions for academic staff. It also impedes the fostering of a true agri-cultural R&D ecosystem with multiple independent actors that collaborate and compete on an equal footing.